Association Behaviour and Physicochemical Properties of Dihydroxystearic Acid and Octyl Dihydroxystearate, and Their Applications in Cosmetics - Mohamed Sopian, Marisol Hainny (2006)
The phase behaviour in ternary system had been studied at 85°C under visual observation by polarizing light and they were confirmed by polarization microscope. It was found spherulite and needles type of crystal for DHSA and Octyl dihydroxystearate respectively. The polymorphs were typically distinguished by differences in their X-ray spectra using X-ray diffraction spectroscopy. Polymorph DHSA and Octyl dihydroxystearate in MCT exist as beta prime (β’) and beta (β). The results also showed that mixture of DHSA/ Octyl dihydroxystearate in different type of third component (MCT and ethanol) may posses only stable β’ form, only stable β form or both β and β’ form. A rheological analysis showed the deformation and flow behaviour of DHSA / Octyl dihydroxystearate and MCT respectively. From hysteresis value, the correlation between the crystal polymorph and decreasing of ratio DHSA plays an important role with the structure breakdown. Instability of polymorph gave vary and unpredictable viscosity value to the mixture of DHSA and Octyl dihydroxystearate. Study of frequency sweep gave idea viscoelastic properties of DHSA and Octyl dihydroxystearate in MCT. Most samples gave result of storage modulus was always higher than the loss modulus (G’>G”). Loss modulus higher than storage modulus (G”>G’) for 30:70 of DHSA/ Octyl dihydoxystearate at 85% MCT.